Molecular Mechanisms Underlying SSRI-induced Non-alcoholic Fatty Liver Disease - Ayyash, Ahmed (My University, 2022)
This thesis aims to investigate fluoxetine, a widely prescribed SSRI antidepressant, for its role in the pathogenesis of NAFLD and uncover novel mechanisms by which it may contribute to drug-induced steatosis. We demonstrated that increased hepatic lipid accumulation was mediated, in part, via elevated serotonin production. The inhibition of hepatic serotonin synthesis prevented lipid accumulation in fluoxetine-treated hepatocytes demonstrating a causal role for serotonin in fluoxetine-induced hepatic steatosis. Interestingly, in several studies, serotonin signaling has been shown to impact prostaglandin biosynthesis. As prostaglandins have been implicated in the development of NAFLD, and fluoxetine has previously been shown to alter the production of prostaglandins I assessed the role of prostaglandins in fluoxetine-induced hepatic lipid accumulation. Fluoxetine treatment increased mRNA expression of prostaglandin biosynthetic enzymes, increased production of prostaglandin 15-deoxy-Δ12,14PGJ2 (PPARG agonist), and elevated PPARG targets involved in fatty acid uptake. Fluoxetine-induced lipid accumulation, 15-deoxy-Δ12,14PGJ2 production, and the expression of PPARG lipogenic genes were attenuated with a PTGS1 specific inhibitor. Taken together these findings suggested that fluoxetine-induced lipid accumulation was mediated via PTGS1 and its downstream product 15-deoxy-Δ12,14PGJ2. Given that Pparg was elevated following fluoxetine treatment, and PPARG regulates microRNA involved in hepatic lipid accumulation, my final project focused on PPARG’s role in altered miRNA expression. Indeed, fluoxetine treatment increased the miRNA expression of miR-122, an effect that was attenuated when fluoxetine treatment was combined with the PPARG antagonist GW9662, suggesting a fluoxetine-PPARG-miR122 axis contributing to hepatic steatosis. While these studies have only been performed in vitro, an understanding of the molecular changes associated with SSRI treatment may lead to the development of strategies to prevent the increased risk of adverse metabolic outcomes associated with the use of SSRI antidepressants.
Keywords: Selective Serotonin Reuptake Inhibitor; SSRI; Fluoxetine; NAFLD; Non-Alcoholic Fatty Liver Disease; Steatosis; de novo Lipogenesis; Serotonin; Metabolic Disorder; Prostaglandin; mir-122; microRNA; peroxisome proliferator-activated receptor gamma; PPARG; 15-deoxy-Δ12,14PGJ2; 15d-PGJ2; Ptgs1; Ptgs2; Liver; MAFLD